2022
DOI: 10.1111/bph.15968
|View full text |Cite
|
Sign up to set email alerts
|

RNA N6‐methyladenosine modifications and potential targeted therapeutic strategies in kidney disease

Abstract: Epigenetic modifications have received increasing attention and have been shown to be extensively involved in kidney development and disease progression. Among them, the most common RNA modification, N6‐methyladenosine (m6A), has been shown to dynamically and reversibly exert its functions in multiple ways, including splicing, export, decay and translation initiation efficiency to regulate mRNA fate. Moreover, m6A has also been reported to exert biological effects by destabilizing base pairing to modulate vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Although the potent functions of METTL3 have attracted increasing attention, the exploration of disease therapies targeting METTL3 is still in its infancy. 41,42 One study revealed that inhibition of METTL3 by the small molecule compound STM2457 is a promising therapeutic strategy for acute myeloid leukemia. 22 Additionally, inhibition of METTL3 by the small molecule compound Cpd-564 significantly reduces renal inflammation, providing a potential therapeutic strategy for AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the potent functions of METTL3 have attracted increasing attention, the exploration of disease therapies targeting METTL3 is still in its infancy. 41,42 One study revealed that inhibition of METTL3 by the small molecule compound STM2457 is a promising therapeutic strategy for acute myeloid leukemia. 22 Additionally, inhibition of METTL3 by the small molecule compound Cpd-564 significantly reduces renal inflammation, providing a potential therapeutic strategy for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Functional and mechanistic exploration serves as the solid foundation for interventional therapeutic studies of diseases. Although the potent functions of METTL3 have attracted increasing attention, the exploration of disease therapies targeting METTL3 is still in its infancy 41,42 . One study revealed that inhibition of METTL3 by the small molecule compound STM2457 is a promising therapeutic strategy for acute myeloid leukemia 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of gene expression patterns controlled by epigenetics can lead to autoimmune diseases, infection, cancers ( Wang et al, 2022 ), inflammatory, autoimmune diseases and a variety of other diseases ( Cui et al, 2022 )and m6A methylation plays an important role in both hypertrophic and ischemic heart disease ( Kumari et al, 2022 ), kidney diseases ( Ni et al, 2023 ), such as renal cell carcinoma, acute kidney injury and chronic kidney disease, osteosarcoma ( Wu et al, 2022 ) and other different types of cancers. In a variety of cancers, m6A was found to play different roles, the same regulator has different functions in different cancers, and even different cell lines of the same cancer, and the phenotypes of regulator interventions with similar functions in the same cancer are also different.…”
Section: Overview Of Rna Modificationmentioning
confidence: 99%
“…Wang, Wang [ 185 ] found that genetic and pharmacological inhibition of METTL3 can significantly reduce renal inflammatory injury and is a potential treatment for AKI. The small molecule compound Cpd564 was virtually screened by high-throughput sequencing and further validated to bind and inhibit METTL3 activity, which could further attenuate renal inflammatory injury [ 186 ]. The anticancer effects of various flavonoids have been revealed [ 148 ].…”
Section: The Clinical Application Of M6a In Renal Injurymentioning
confidence: 99%